AB0587 Pulmonary Arterial Hypertension as A Risk Factor for Mortality in Connective Tissue Disease with Biopsy Proven Interstitial Lung Disease. (15th July 2016) - Svensson, A.L.; Tvede, N.; Carlsen, J.; Iversen, M.; Jensen, A.S.; Jacobsen, S.
Abstract : Background: Connective tissue diseases (CTD) are a heterogeneous group of autoimmune systemic diseases characterized by circulating autoantibodies and varying degrees of organ involvement including interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH). 1–2 PAH in CTD is known to be associated with increased mortality. Whether ILD alone is associated with increased mortality is uncertain, but lung infections have been suggested to accelerate the development of ILD and impair the prognosis. Objectives: To investigate a cohort of CTD patients with biopsy verified ILD and examine whether histopathologic ILD patterns, PAH and/or lung infections requiring hospital admission are independent predictors of mortality. Methods: A retrospective cohort study of CTD patients with lung biopsy verified ILD. Data regarding ILD patterns were obtained from lung biopsies, PAH was evaluated with transthoracic echocardiography (TTE) using tricuspidal regurgitation ≥36 mmHg as a parameter for PAH. Data regarding lung infections requiring hospital admission and death were obtained from medical records. Survival was analyzed by age and gender adjusted multiple cox-regression analysis using SPSS version 22. Results: Fifty-six CTD patients had ILD verified CTD, 21 (37%) with systemic sclerosis, 14 (25%) with polymyositis, 14 (25%) with undifferentiated connective tissue disease and 7 (13%) with mixed connective tissue disease. At the time of lung biopsy, the 56 CTD patients (50% females) had a mean (SD) age of 53.5 (11.3) years and disease duration of 4.4 (9.1) years. The follow-up after biopsy consisted of 203 person-years. Eight patients (14%) died during follow-up translating to a mortality rate of 39.4 per 1000 person years. Non-specific interstitial pneumonia (NSIP) histopathological pattern was observed in 15 (27%), fibrosis in 16 (29%), while 25 (44%) had other histopathological patterns. Thirteen (23%) patients had PAH which was associated with increased mortality with a HR=5.3 [95% CI 1.2–24.2], p=0.03. The patients with histopathological NSIP and fibrosis patterns had a higher mortality than other types of ILD, nevertheless the histopathologic pattern of ILD and hospital admission requiring infections did not predict increased mortality. Conclusions: PAH predicts poor outcome in CTD patients with ILD, irrespective of the histopathological ILD pattern. In CTD with interstitial lung disease early PAH screening and initiation of treatment is paramount for optimizing survival among patients with CTD and ILD. References: Khanna D. et al. Arthritis Rheum. 2013 December; 65 (12): doi: 10.1002/art.38172 Solomon J.J. and Fisher A. Journal of Intensive Care Medicine 2015, vol. 30 (7) 392–400: doi: 10.1177/0885066613516579 Galié N. et al. European Heart Journal (2016) 37, 67–119. doi: 10.1093/eurheartj/ehv3172) Yoshida S. Allergology International. 2011;60:405–409. Disclosure of Interest: None declared